Normative value of adductor squeeze test in Nepali male professional football players: A cross-sectional study - Adhikari, Umesh; Humagain, Yubaraz Prasad Sharma; Shrestha, Rajan (Birat Journal of Health Sciences, 2022)
Introduction: Groin pain is a common problem. Adductor squeeze test are used to diagnosed, monitor and prophylactically determine the risk of developing groin pain. Objectives: The aim of study was to establish normative adductor squeeze test values in Nepali male professional football players. Methodology: One hundred and sixty-one healthy players from top football clubs attended the study. Hip adductor muscle strength was assessed using sphygmomanometer at 0⁰, 45⁰ and 90⁰ hip flexion. Results: The mean value of adductor squeeze test score at 0⁰ of hip flexion position was 152.03 ± 33.18, for 45⁰ of hip flexion position was 152.38 ± 27.52 and for 90⁰ of hip flexion position was 120.57 ± 21.88. 45⁰of hip flexion has the highest value of the adductor squeeze test. Conclusion: This study established reference ranges for adductor squeeze tests for normative pre-season data in Nepali male A-division professional football players.